Evaluation of functional properties of skeletal muscle using functional magnetic resonance imaging (fMRI) - Hiroshi Akima (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Muscle functional magnetic resonance imaging (mfMRI) is a powerful tool for the visualization of anatomical and functional properties (e.g. levels and patterns of activation) of human skeletal muscles. Fleckenstein et al.1) first reported that working muscles exert acute effects on MRI signals in 1988, and since this time a lot of attempts have been made to assess function and metabolism of activated muscles in healthy and diseased individuals. This review focuses on five aspects of mfMRI; 1) The relation between mfMRI and other functional parameters of working muscles; 2) Muscle activation patterns during single- and multi-joint exercises; 3) The effect of resistance training on mfMRI; 4) The effect of disuse on mfMRI; and 5) The assessment of inhomogenous activation within a single muscle by mfMRI. Finally future application and potential contribution of mfMRI are discussed.